Comparison Between Rectangular and Cylindrical Continuous Ohmic Heating Modelling - Salih, Elzubier Ahmed; Spotar, Sergey (Gezira Journal of Engineering and Applied Sciences, 2018)
Two-dimensional models is developed for collinear cylindrical continuous ohmic heating cell (3-ring electrode inserted in cylindrical column one at the middle and the other two at extremities) and rectangular continuous ohmic heating (two parallel plate electrode inserted along 0.5m long) to simulate the Electric field distribution, temperature and velocity profiles during continuous ohmic heating of non-Newtonian power law liquid food (Guava juice) using computational fluid dynamic (CFD) codes using A user defined functions (UDFs) which is employed in original flat pattern FLUENT 6.1 for electric field equation. The simulation was carried with and without buoyancy driven force effects. The buoyancy effects show significance effect in both colliner and parallel plate electrodes configuration ohmic heating in this study, the parallel plate electrode configuration (transverse electric fields) ohmic heating show uniform temperature distribution than the collinear one. The computations domain used for the cylindrical heating cell (with diameter of 0.05m and height of 0.50m, and have three electrodes, each electrode have width of 0.02m and the distances between electrode is 0.22m) and the rectangular heating cell (with length of 0.2m, width of 0.04m and height 0.6m, the plate electrode is 0.2m×0.04m×0.6m inserted along the wall) . In the rectangular ohmic heating the flow behavior measurement was used to validate the CFD simulation using water in the temperature range 30- 40 0C and in the cylindrical ohmic heating for guava juice in temperature range 30-900C.